Combined analysis of global and compartmental brain volume changes in early multiple sclerosis in clinical practice. (March 2016) - Pichler, A; Khalil, M; Langkammer, C; Pinter, D; Bachmaier, G; Ropele, S; Fuchs, S; Enzinger, C; Fazekas, F
Background: The extent and clinical significance of brain volume changes in different phases of multiple sclerosis (MS) is still under discussion. Objective: To determine the rate of global and compartmental brain volume changes in patients with a clinically-isolated syndrome (CIS) compared to patients with definite MS, by long-term follow-up and as a predictor of conversion to MS in a routine clinical setting. Methods: We investigated 120 patients (63 CIS and 57 MS) at baseline and after a mean follow-up period of 43 months, including detailed clinical examination and 3-Tesla magnetic resonance imaging (MRI). Our imaging analyses comprised the normalized brain volume (NBV), cortical grey matter (cGMV) and white matter (WMV) volumes using SIENA/X, the percentage of brain volume change (PBVC) using SIENA and the change in the volume of the thalami (TV) and basal ganglia (BGV). We also determined the amount and change of T2-lesion load (T2-LL). Results: At baseline, all the brain volume metrics, except cGMV, were significantly lower; and the T2-LL was significantly higher, in patients with MS rather than CIS. During the follow-up, only the PBVC was higher in MS ( p = 0.008) and this difference was driven by converters from CIS to MS. Quartiles of PBVC did not allow us to predict conversion to MS, but were associated with the degree of disability. Conclusions: PBVC is the most sensitive marker of progressing atrophy and a higher PBVC was generally associated with more active disease; however, it did not serve to predict the course of MS on an individual basis, in this study.